(untitled) (OJS 3.5 Testdrive Journal, 2021)
Vaccines for a long time have been used to prevent influenza. They are often recommended for healthy adults before an influenza season, despite the low risk of complications due to this infection in them. The article reviews the rationale for such recommendations.